Targeting Recovery in Persistent Persecutory Delusions: A Proof of Principle Study of a New Translational Psychological Treatment (the Feeling Safe Programme). Issue 5 (5th April 2016) - Freeman, Daniel; Bradley, Jonathan; Waite, Felicity; Sheaves, Bryony; DeWeever, Natalie; Bourke, Emilie; McInerney, Josephine; Evans, Nicole; Černis, Emma; Lister, Rachel; Garety, Philippa; Dunn, Graham
Abstract : Background: Many patients do not respond adequately to current pharmacological or psychological treatments for psychosis. Persistent persecutory delusions are common in clinical services, and cause considerable patient distress and impairment. Our aim has been to build a new translational personalized treatment, with the potential for wide use, that leads to high rates of recovery in persistent persecutory delusions. We have been developing, and evaluating individually, brief modular interventions, each targeting a key causal factor identified from our cognitive model. These modules are now combined in "The Feeling Safe Programme".Aims: To test the feasibility of a new translational modular treatment for persistent persecutory delusions and provide initial efficacy data.Method: 12 patients with persistent persecutory delusions in the context of non-affective psychosis were offered the 6-month Feeling Safe Programme. After assessment, patients chose from a personalized menu of treatment options. Four weekly baseline assessments were carried out, followed by monthly assessments. Recovery in the delusion was defined as conviction falling below 50% (greater doubt than certainty).Results: 11 patients completed the intervention. One patient withdrew before the first monthly assessment due to physical health problems. An average of 20 sessions ( SD = 4.4) were received. Posttreatment, 7 out of 11 (64%) patients had recovery in their persistent delusions. Satisfaction ratings were high.Conclusions: The Feeling Safe Programme is feasible to use and was associated with large clinical benefits. To our knowledge this is the first treatment report focused on delusion recovery. The treatment will be tested in a randomized controlled trial.